PENGARUH PEMBELAJARAN BERDIFERENSIASI KONTEN BERBANTUAN MICROLEARNING TERHADAP KEMAMPUAN MENULIS TEKS PIDATO SISWA SMPN 4 KOTA SUKABUMI - Saprudin, Anastacia Salwa; Firdaus, Asep; Humaira, Hera Wahdah (Universitas Muhammadiyah Surabaya, 2025)
This research is motivated by the existence of problems in writing speech texts. The factor behind this is because students still have difficulty in understanding the structure and also difficulty in expressing ideas in stringing the words of the speech text. This study aims to determine the effect of the application of differentiated learning combined with microlearning on the ability to write speech texts of SMPN 4 Kota Sukabumi students. This study uses quantitative methods with Pre-Experimental Designs. The sample consisted of two classes selected based on certain characteristics, namely control class and experimental class. Data collection was conducted by means of tests, observation, and documentation. The data obtained was then analyzed using the t-test. The results showed that there was a significant difference between the control class and the experimental class. This can be seen in the results of the essay test in the form of a posttest in making pidto text based on its structure carried out in each class. The control class obtained an average score of 74.24 with a sufficient category. While the experimental class obtained an average score of 80.30 in the good category. This identifies that product differentiated learning assisted by microlearning is effective in improving the ability to write speech text. Thus, product differentiated learning assisted by microlearning on the ability to write speech texts can be used to improve the ability to write speech texts.